A participação dos negros escravizados/libertos na Cabanagem entre os anos de 1835 a 1840 - SANTOS, Roseane Araújo dos (2022)
The purpose of this article is to identify how the participation of enslaved/freed blacks took place in the revolt called Cabanagem, which broke out on January 7, 1835 to 1840 with the “defeat” of the Cabanos. It is intended to analyze the demands that this population brought to the Cabano movement, explore where most of the slaves departed from, how they claimed social issues during the revolt and how they were mentioned in the documents of the rulers of the period, due to the fact that that the enslaved blacks served as a mere instrument of work for the owners of ranches and farms in the region. It is also considered to discuss why this condition lasted for so long and for what reasons these subjects were hidden from historiography and the reflection of this concerning their marginalization.